2020
DOI: 10.1177/2048872619896063
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers predictive of late cardiogenic shock development in patients with suspected ST-elevation myocardial infarction

Abstract: Background: Cardiogenic shock complicating ST-elevation myocardial infarction is characterised by progressive left ventricular dysfunction causing inflammation and neurohormonal activation. Often, cardiogenic shock develops after hospital admission. Whether inflammation and a neurohormonal activation precede development of clinical cardiogenic shock is unknown. Methods and results: In 93% of 2247 consecutive patients with suspected ST-elevation myocardial infarction admitted at two tertiary heart centres, admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The present study showed that high bio-ADM at ICU admission in patients with CS complicating AMI was associated with increased mortality at 30 days. There have been several studies investigating the prognostic impact of adrenomedullin in patients with CS [ 30 , 31 , 32 ]. However, the majority of these studies used a stable fragment of the precursor molecule, mid-regional pro-ADM (MR-proADM) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that high bio-ADM at ICU admission in patients with CS complicating AMI was associated with increased mortality at 30 days. There have been several studies investigating the prognostic impact of adrenomedullin in patients with CS [ 30 , 31 , 32 ]. However, the majority of these studies used a stable fragment of the precursor molecule, mid-regional pro-ADM (MR-proADM) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, assessing copeptin in patients with STEMI could be of prognostic importance: findings from a cohort of 401 patients with STEMI undergoing primary percutaneous coronary intervention showed copeptin levels at admission were significantly higher in non-survivors than in survivors (154.8 vs. 30.3 pmol/L) [104]. Moreover, in a cohort of more than 2000 patients with suspected STEMI, copeptin levels at admission were significantly higher in those complicating with cardiogenic shock (444 and 141 pmol/L in patients with early and late cardiogenic shock, respectively, vs. 55 pmol/L, p < 0.0001) and were independent predictors for late cardiogenic shock development, although with the lowest performance among the considered biomarkers (AUC 0.660 at cut-off values > 138 pmol/L) [105]. Data from a recent metaanalysis including 2269 patients from six studies indicate copeptin may be of prognostic importance in overall acute coronary syndrome, since it has been associated to mortality with acceptable predictive performance (AUC 0.730) [106].…”
Section: Heart Failure and Acute Myocardial Infarctionmentioning
confidence: 96%
“…In this issue of the European Heart Journal: Acute Cardiovascular Care, three reports help illustrate a path towards refined risk stratification in this population. [5][6][7] A focused clinical history and basic physical and laboratory findings remain remarkably useful for risk stratification of patients with suspected ACSs. Previously, the thrombolysis in myocardial infarction (TIMI) simple risk index (heart rate (HR) × (age/(10)) 2 /systolic blood pressure (SBP)) was developed to stratify early mortality risk in ST-segment elevation myocardial infarction (STEMI) patients.…”
mentioning
confidence: 99%
“…In another important report from this issue, Frydland et al demonstrate the application of novel biomarkers to enhance the performance of the ORBI score. 6 In particular, Frydland et al found that in 2247 initially stable patients with STEMI, copeptin, mid-regional pro-adrenomedullin (MRproADM) and pro-atrial natriuretic peptide (proANP) added to the ORBI score for predicting late-onset cardiogenic shock. 6 Each of these biomarkers had a negative predictive value of 98% or greater and, when adjusted for the ORBI risk score, were associated with late-onset shock (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation